2001
DOI: 10.1007/s15010-001-1098-7
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization Activity and Persistence of Antibodies Induced in Response to Vaccination with a Novel Mumps Strain, RIT 4385

Abstract: These data suggest that both vaccines provided equivalent protection against mumps over this 18-month period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…For mumps and rubella antibodies, our results seem to be better than those with MMR II. Similarly, the degree of persistence of mumps antibodies in our study was higher than those reported by Usonis et al (9).…”
contrasting
confidence: 61%
“…For mumps and rubella antibodies, our results seem to be better than those with MMR II. Similarly, the degree of persistence of mumps antibodies in our study was higher than those reported by Usonis et al (9).…”
contrasting
confidence: 61%
“…The decline of immunity to these viruses after administration of a first dose of MMRV vaccine was comparable to that in the control group of children who had received a first dose of a standard MMR vaccine during the second year of life and in keeping with the results of previous studies of antibody persistence after a first dose of MMR. 17,18 The 85% of subjects in the MMRV group seropositive for varicella antibodies 4 to 5 years after administration of the first vaccine dose (all had been seropositive 6 weeks after the first dose) are in keeping with the results of other studies of antibody persistence following varicella vaccination 8,10,19 as well as estimates of vaccine efficacy after a single dose (87% overall ͓95% CI: 81-91%͔; 97% in the first year after vaccination declining to 84% 2-8 years after vaccination) 6 supporting the need for administration of a second dose of varicella vaccine for optimum protection. 9 In this study, administration of a second dose of MMRV vaccine was immunogenic in children who had previously received a first dose of this vaccine and in those who had received a first dose of a standard MMR vaccine during the second year of life.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although the serologic correlate of protection induced by mumps vaccination has not been accepted yet, the neutralizing antibodies have been considered as the most probable candidate. [22][23][24][25][26] Regarding animal models, although guinea pigs, mice, cotton rats, rabbits and hamsters are not susceptible to MuV infection, they do generate neutralizing antibodies upon mumps administration. 27 In such a situation, we chose to establish and optimize immunogenicity assay in guinea pigs measuring quantity of functional virus-specific antibodies raised upon immunization of animals with MuV.…”
Section: Introductionmentioning
confidence: 99%